On the approximation and growth of entire harmonic functions in R_n - Veselovskaya, O. V. (Ukrains’kyi Matematychnyi Zhurnal, 2018)
We establish a criterion of extendability of harmonic function in a ball of the n-dimensional space to harmonic entire function and study the growth of entire harmonic function in terms of the best approximation of these function by harmonic polynomials.